The enhancement of immunoactivity induced by immunogenic cell death through serine/threonine kinase 10 inhibition: a potential therapeutic strategy - Xia, Xiaoli; Wang, Yixin; Wang, Minghui; Lin, Jian; Wang, Ruiheng; Xie, Shufeng; Yu, Yaoyifu; Long, Jinlan; Huang, Zixuan; Xian, Huajian; Zhang, Wenjie; Lu, Chaoqun; et al. (Frontiers in Immunology, 2024)
The patient samples procured from the TARGET AML database can be stratified into two subgroups based on the expression levels of immunogenic cell death (ICD) genes: ICD-high and ICD-low. In the ICD-high subtype, there was a notable increase in the abundance of immune cell populations, along with the enrichment of pathways pertinent to the activation of various immune cells. Despite these immunological enhancements, this subgroup demonstrated a poorer prognosis. This phenomenon was consistently observed across various additional AML datasets, leading us to hypothesize that elevated expression of ICD genes does not invariably correlate with a favorable prognosis. Notably, STK10 exhibited elevated expression in AML, was associated with a poor prognosis, and exhibited synchronous expression patterns with ICD genes. Inhibition of STK10 led to the activation of ICD and the induction of an anti-tumor response. Moreover, when combined with other ICD inducers, it produced a synergistic anti-tumor effect. Our results reveal the impact of STK10 on ICD and underscore its key role in initiating ICD.